The Hikmah Method - salmadanis salmadanis (Universitas Islam Negeri Imam Bonjol Padang, 2005)
Every elements of dakwah attentively and systematically were explained in Al-Qur'an. To implement in society, it needs special methods. Dakwah perspective in Al-Qur'an doesn't only manage the dakwah activities, but also gives specific ways in facing specific society. One of the methods is hikmah. There are 20 hikmah words in Al-Quran with all forms They can be found in many suurah, Eke al-Nahl 125, al Qamar: 5 Shad: 20, al-lara: 39, Luqman: 12, al-Zukhrut 63. al-Bagerah: 129,151 ,31, and 269, All Imran 81, 164, al-Nisa 113 al-Anzab: 34, a -Jumu'ah: 2 al Maidah: 110, etc There are also many variations from mufassir in understanding the hikmah as written on this article. The writer discusses the understanding of most mufassir, and concludes the meaning of hikmah